Understanding cellulose dissolution： effect of the cation and anion structure of ionic liquids on the solubility of cellulose - Zhang, Jinming; Xu, Lili; Yu, Jian; Wu, Jin; Zhang, Xiaoyu; He, Jiasong; Zhang, Jun (Science China. Chemistry, 2016)
The effect of ionic liquids（ILs） on the solubility of cellulose was investigated by changing their anions and cations. The structural variation included 11 kinds of cations in combination with 4 kinds of anions. The interaction between the IL and cellobiose, the repeating unit of cellulose, was clarified through nuclear magnetic resonance（NMR） spectroscopy. The reason for different dissolving capabilities of various ILs was revealed. The hydrogen bonding interaction between the IL and hydroxyl was the major force for cellulose dissolution. Both the anion and cation in the IL formed hydrogen bonds with cellulose. Anions associated with hydrogen atoms of hydroxyls, and cations favored the formation of hydrogen bonds with oxygen atoms of hydroxyls by utilizing activated protons in imidazolium ring. Weakening of either the hydrogen bonding interaction between the anion and cellulose, or that between the cation and cellulose, or both, decreases the capability of ILs to dissolve cellulose.